2017
DOI: 10.21597/jist.2017.223
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Variance Components and Genetic Trend for the Race Performance in Turkish Arabian horse

Abstract: ÖZET: Bu araştırmada, Türk Arap atında yarış performansı özellikleri için varyans komponentleri ve genetik yönelim tahmin edilmiştir. Bunun için Türkiye 'de 1990-2016 arasında koşan 8321 atın 35929 yarış sonucu değerlendirilmiştir. Varyans komponentleri REML, damızlık değerler BLUP Animal modelde MTDFREML ile tahmin edilmiştir. En iyi yarış zamanı ve yarış hızı üzerine mesafe, cinsiyet, pist tipi, yaş, yarış yılı ve şehir etkileri önemlidir. Belirlenen modellerde en iyi yarış süresi ve hız için kalıtım derece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Kaygisiz et al, (2011) found that the phenotypic correlations between the features examined were generally significant (P <0.01), while the correlations between the birth weight and the investigated features were not. Duru et al, (2017) found that direct maternal genetic correlations for cidago height, chest circumference and shank circumference were -0.15, -0.99 and -0.42, and genetic correlations between features ranged between 0.68 and 0.71.…”
Section: Resultsmentioning
confidence: 95%
“…Kaygisiz et al, (2011) found that the phenotypic correlations between the features examined were generally significant (P <0.01), while the correlations between the birth weight and the investigated features were not. Duru et al, (2017) found that direct maternal genetic correlations for cidago height, chest circumference and shank circumference were -0.15, -0.99 and -0.42, and genetic correlations between features ranged between 0.68 and 0.71.…”
Section: Resultsmentioning
confidence: 95%